Influência do modo de aplicação e viscosidade do ácido fosfórico 37% na adesão de pinos de fibra de vidro em condutos radiculares - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The aim of the present study was to evaluate the influence of the etchant viscosity (liquid or gel) and the application mode (passive or sonic) on the pushout bond strength values of fiberglass post to root dentin and the conditioning pattern on the smear-layer covered root dentin before cementation. The roots of premolars were prepared endodontically and divided into 4 groups (n = 8) according to the combination of the main factors: phosphoric acid viscosity (liquid gel) and application mode (passive or sonic). After the application of the universal adhesive into the root canals, the fiberglass posts were cemented with cementation system RelyX ARC. Then, the roots were sectioned transversely 6 slices of approximately 1 mm and the push-out test performed at a speed 0.5 mm/min. The results were submitted to a repeated measures three-way ANOVA and Tukey’s test (alpha = 0.05). The cross-product interaction mode of application vs. etchant viscosity (p = 0.0002) and the main factor root third (p < 0.0001) were statistically significant. The highest bond strength value was observed when the conditioning of the root canal was performed with a liquid phosphoric acid under sonic application mode (p < 0.05), being all other groups similar one another (p < 0.05). Regarding the root third, the highest push-out bond strength value was observed in the cervical third, followed by the medium third and the apical thirds (p < 0,05). The most common fracture pattern was the mixed failure. By the partial results one may conclude that a better bonding of fiberglass posts to root canals can be achieved when the conduits are conditioned with a
Keywords: Pinos Dentários; Ácidos Fosfóricos; Ataque Ácido Dentário; Técnica para Retentor Intra-radicular; Dental pins; Phosphoric acids; Acid etching; Dental; Post and core technique; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA